2015
DOI: 10.1371/journal.pone.0123932
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effect of Neuroserpin in Oxygen-Glucose Deprivation- and Reoxygenation-Treated Rat Astrocytes In Vitro

Abstract: Neuroserpin (NSP) reportedly exerts neuroprotective effects in cerebral ischemic animal models and patients; however, the mechanism of protection is poorly understood. We thus attempted to confirm neuroprotective effects of NSP on astrocytes in the ischemic state and then explored the relative mechanisms. Astrocytes from neonatal rats were treated with oxygen-glucose deprivation (OGD) followed by reoxygenation (OGD/R). To confirm the neuroprotective effects of NSP, we measured the cell survival rate, relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…Previous research has shown that both a reduced rate of cell survival and an enhanced LDH release can be observed in OGD/R-treated astrocytes [30]. Astrocytes apoptosis may contribute to the pathogenesis of a number of acute and chronic neurodegenerative disorders, such as cerebral ischemia, Alzheimer’s disease and Parkinson’s disease [31].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that both a reduced rate of cell survival and an enhanced LDH release can be observed in OGD/R-treated astrocytes [30]. Astrocytes apoptosis may contribute to the pathogenesis of a number of acute and chronic neurodegenerative disorders, such as cerebral ischemia, Alzheimer’s disease and Parkinson’s disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that the expression of p-ERK1, p-ERK2, p-IKKBα/β and P65 proteins is upregulated in OGD/R-treated rat astrocytes [30]. Previous scholars have found that this phytochemical PYC inhibits NF-κB activation in preventing the atherogenic process [33].…”
Section: Discussionmentioning
confidence: 99%
“…The NSP-induced amelioration could be significantly reversed by the administration of sc3060, an NF-κB pathway inhibitor. Thus, we concluded that the inhibition of NF-κB signaling pathways may be a potential mechanism in the protective effects of NSP on astrocytes [11]. Neurons and microglia are the other important components in the brain.…”
Section: Introductionmentioning
confidence: 76%
“…The OGD/R processes were performed as previously described [11,22,23], with minor modifications. Briefly, the original glucose-containing media were removed from all treatment groups and kept aside for future use.…”
Section: Processes Of Oxygen-glucose Deprivation Followed By Reoxygenmentioning
confidence: 99%
See 1 more Smart Citation